Selection of antagonistic actinomycete isolates as biocontrol agents against root-rot fungi - Erginbas, Gul (2010)
In this study, actinomycetes isolates, isolated from rhizosphere of wheat (Triticum aestivum L.), were screened for antagonistic activities on certain root rot fungi (Fusarium culmorum, Fusarium graminearum, Fusarium verticilloides and Bipolaris sorokiniana). The  in vitro antagonistic effects of actinomycetes isolates were determined on solid media against fungal pathogens. The inhibition mechanism, effect of application time and pH on inhibition was investigated. The actinomycete isolate 129.01 exhibited a high inhibition ratio of more than 60 % against all fungi. The activity of the isolate 129.01 against root rot fungi was tested under greenhouse conditions. The root rot score (1-10), mean plant height (cm) and mean weight of green part of plant (g) were determined after an incubation period. The root rot score of the infected plants was decreased significantly by this isolate, even if the plants were inoculated with all of the pathogen fungi together (P<0.05). The results indicate that isolate 129.01 could be useful as a biocontrol agent. The assignment of the isolate 129.01 to the genus Streptomyces was supported by 16S rRNA analysis.